Covid-19 Pandemisinde Mikrobiyoloji Laboratuvar Tanı Metodları - (:unkn) unknown (My University, 2020)
Endemi düzeyinde kalan SARS-CoV ve MERS'i takiben, SARS-CoV-2, 2020 başında, Çin Halk Cumhuriyeti'nin Wuhan eyaletinden yayılarak pandemiye sebep olmuştur. Diğer insan koronavirüslerinden klinik ve laboratuar farklılıklar gösteren SARS-CoV-2'de tanısal işlemlerin optimum zamanlaması, tanı yöntemleri konularında araştırmalar devam etmektedir. Hastalığın tanısında ve takibinde PCR ve serolojik testler kullanılmaktadır. Bu derlemede COVID-19 pandemisinde mikrobiyoloji laboratuvar tanı yöntemleri güncel literatür ile özetlendi.

Following SARS-CoV and MERS, which remained at the endemic level, SARS-CoV-2 spread from Wuhan province of the People’s Republic of China in early 2020, causing the pandemic._x000D_ Researches continue on the optimum timing of diagnostic procedures and diagnostic methods in SARS-CoV-2, which shows clinical and laboratory differences from other human coronaviruses. PCR (polymerase chain reaction) and serological tests are used in the diagnosis and follow-up of the disease. In this review, microbiology laboratory diagnosis methods in the COVID-19_x000D_ pandemic were summarized with the current literature.
Microbiology Laboratory Diagnostic Methods in Covid-19 Pandemic